Resiliencia en el abuso sexual. - Peñafiel Lituma, Tatiana Fabiola (2015)
Objective of this research is to characterize the levels of resilience in a victim of sexual abuse, based on the theoretical approach of the Positive Psychology to learn about the dimensions of the object studied resilient which is comprised of a 25-year-old woman, using the methodology employed in the research process is mixed, analytical and biographical. To obtain information relevant to the topic investigated, applied the Resilience Scale of Wagnild & Young, a history personológica and a semistructured interview. The results show a moderate resilience, which has its support in the family and social relations that surround the patient. In addition, according to the results of the scale applied, the resilient characteristics which the subject of research presents and that at the time helped him to overcome the traumatic event are: feel good only, self-confidence and perseverance. From the results and the arduous consultation updated bibliographic and scientific order, it was concluded that the level of resilience in the victim of sexual abuse determines the strength with which exceeds the traumatic event, being the family and the social context, factors that contribute positively in this process.